Optimalisasi Peran Mahasiswa Kuliah Kerja Nyata Dalam Meningkatkan Jiwa Kewirausahaan Melalui Pemanfaatan Limbah Barang Bekas Pada SMPN 1 Bolo - Pratiwi, Aliah; Ernawati , Sri; Firdaus , Muhammad; Apriyani, Annisa; Suciyati, Novita; Rizki Mauludin , M (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2024)
Abstract This research aims to optimize the role of Real Work Lecture (KKN) students in increasing students' entrepreneurial spirit through the use of used goods waste at Pertam High School (SMP) Negeri 1 Bolo. This program focuses on teaching assistance, where KKN students provide guidance related to the basic concepts of entrepreneurship and direct practice in processing used goods into useful products. The methods used include lectures, discussions and experiments, with a program duration of 4 weeks. The results of this program show an increase in students' interest and creativity in entrepreneurship as well as an understanding of the importance of innovation in utilizing waste. This program not only helps reduce environmental pollution but also opens up economic opportunities.